Challenges and Opportunities to Regional Renewal in the European Union. (January 2021) - Pontarollo, Nicola; Serpieri, Carolina
The strength of the 2008 financial and economic crisis and the resulting degree of resilience were heterogeneous among and within the European Union countries. Challenges and opportunities driven by regional-specific differences determined the ability to overshoot the precrisis levels of growth. Focusing upon Nomenclature of Territorial Units for Statistics 2 (NUTS 2) European regions, we explore a novel conceptual framework related to regional economic resilience, namely the renewal capacity. Precisely, we concentrate on the capacity of regional economies to "renew" their growth paths in the labor market in the aftermath of the recent global crisis. We find some well-identified spatial patterns of regional employment renewal and we identify a set of territorial assets that allow regions to bounce back faster and more comprehensively than others to the economic downturn. Furthermore, there are significant differences between the drivers of the regional renewal of Old and New Member States. Our findings suggest potential policy directions at all levels for enhancing regional resilience.